Robust stochastic stability - Carlos Ferrer-Alós; Nick Netzer (University of Zurich, Department of Economics, 2014)
A strategy profile of a game is called robustly stochastically stable if it is stochastically stable for a given behavioral model independently of the specification of revision opportunities and tie-breaking assumptions in the dynamics. We provide a simple radius-coradius result for robust stochastic stability and examine several applications. For the logit-response dynamics, the selection of potential maximizers is robust for the subclass of supermodular symmetric binary-action games. For the mistakes model, the weaker property of strategic complementarity suffices for robustness in this class of games. We also investigate the robustness of the selection of risk-dominant strategies in coordination games under best-reply and the selection of Walrasian strategies in aggregative games under imitation.
Keywords: C72; D83; 330; learning in games; stochastic stability; radius-coradius theorems; logit-response dynamics; mutations; imitation